Different parameters affecting body weights of Charolais and Limousine calves from birth to weaning - Simčič, Mojca; Malovrh, Špela; Čepon, Marko (Acta Agraria Kaposváriensis, 2006)
Birth weight and body weight at the beginning, in the middle and at the end of grazing season of Charolais (312) and Limousine (167) calves at the Educational and Research Animal Husbandry Centre Logatec (Slovenia) born from 1995 to 2005 were analysed. Fixed effect of breed, sex, parity, year, age of calves and random animal effect were included. Breed, sex and year influenced birth weight and body weight at the beginning, in the middle and at the end of grazing season. Parity influenced only birth weight and body weight at the beginning of grazing season. Age of calves influenced body weight at the beginning and in the middle of grazing season, but this effect was not shown at the end of grazing season. Variance and covariance components for direct additive genetic effect were estimated by REML method in the VCE5 package. Estimated heritability for birth weight, body weight at the beginning, in the middle and at the end of grazing season were 0.62; 0.25; 0.25 and 0.26, respectively. Genetic correlation with birth weight for body weight at the beginning was 0.78, for body weight in the middle was 0.51 and for body weight at the end of grazing season was 0.40.